2015
DOI: 10.1002/btpr.2118
|View full text |Cite
|
Sign up to set email alerts
|

Poly-γ-glutamic acid produced fromBacillus licheniformisCGMCC 2876 as a potential substitute for polyacrylamide in the sugarcane industry

Abstract: As an environmentally friendly and industrially useful biopolymer, poly-γ-glutamic acid (γ-PGA) from Bacillus licheniformis CGMCC 2876 was characterized by the high-resolution mass spectrometry and (1)H NMR. A flocculating activity of 11,474.47 U mL(-1) obtained with γ-PGA, and the effects of carbon sources, ions, and chemical properties (D-/L-composition and molecular weight) on the production and flocculating activity of γ-PGA were discussed. Being a bioflocculant in the sugar refinery process, the color and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As illustrated in Fig. 3 a, glycerol metabolism was markedly inhibited by the addition of glucose, while glycerol was used as a preferred carbon source in γ-PGA synthesis, which was consistent with the reports of some other studies [ 6 , 15 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As illustrated in Fig. 3 a, glycerol metabolism was markedly inhibited by the addition of glucose, while glycerol was used as a preferred carbon source in γ-PGA synthesis, which was consistent with the reports of some other studies [ 6 , 15 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 90%
“…In our previous studies, B . licheniformis CGMCC2876 was observed to produce extracellular polysaccharides when using glucose as the sole carbon source [ 13 , 14 ], whereas poly-γ-glutamic acid (γ-PGA) was secreted when trisodium citrate and glycerol were used as the carbon sources [ 15 ]. Both of the extracellular polymeric substances exhibited high flocculating activities.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, γ-PGA can be released into the environment to sequester toxic metal ions, decrease salt concentration [ 4 ], provide a carbon source [ 15 ], and protect against adverse conditions [ 16 ]. γ-PGA can also improve the formation of biofilms and assist absorption of essential nutrients from the environment [ 17 ].…”
Section: Overview Of γ-Pgamentioning
confidence: 99%
“…By using the same strain, Yan et al demonstrated the potential of the bio-flocculant activity of γ-PGA to replace polyacrylamide from the sugarcane industry for clarification. The presence of metal ions such as Mg 2+ could enhance the flocculating ability and γ-PGA production, unlike B. subtilis NX-2, which requires Mn 2+ ions [33]. Bajaj et al reported the ability of metabolic precursors to improve the molecular size and yield of γ-PGA by B. licheniformis NCIM 2324.…”
Section: Bacillus Licheniformismentioning
confidence: 99%